Small genome size and variation in ploidy levels support the naturalization of vascular plants but constrain their invasive spread - Pysek, Petr; Lucanova, Magdalena; Dawson, Wayne; Essl, Franz; Kreft, Holger; Leitch, Illia J.; Lenzner, Bernd; Meyerson, Laura A.; Pergl, Jan; van Kleunen, Mark (My University, 2023)
Karyological characteristics are among the traits underpinning the invasion success of vascular plants. Using 11 049 species, we tested the effects of genome size and ploidy levels on plant naturalization (species forming self-sustaining populations where they are not native) and invasion (naturalized species spreading rapidly and having environmental impact). The probability that a species naturalized anywhere in the world decreased with increasing monoploid genome size (DNA content of a single chromosome set). Naturalized or invasive species with intermediate monoploid genomes were reported from many regions, but those with either small or large genomes occurred in fewer regions. By contrast, large holoploid genome sizes (DNA content of the unreplicated gametic nucleus) constrained naturalization but favoured invasion. We suggest that a small genome is an advantage during naturalization, being linked to traits favouring adaptation to local conditions, but for invasive spread, traits associated with a large holoploid genome, where the impact of polyploidy may act, facilitate long-distance dispersal and competition with other species.
Keywords: distribution; genome size; naturalization; plant invasions; polyploidy; species traits; 570